Mapping the Condition of Seagrasses Beds in Ternate -Tidore Waters, and Surrounding Areas - Simon I. Patty (Sam Ratulangi University, 2016)
Seagrass beds is one of the most prolific shallow water ecosystems, having ecological function in the life of the various marine organisms and other coastal systems. Data and information of seagrass condition in the waters of Ternate, Tidore and surrounding areas are still hardly unexplored. This study aimed to describe the spatial distribution information of seagrass cover percentage, seagrass conditions and environmental characteristics. The basic data used for mapping of seagrass is Landsat 8 on a path 110 row 59 recordings in July 2015. Analysis of overlaying and the interpretation of the seagrass distribution software using